A bibliometric analysis of fiber cement board research: Trends, development and future direction (Journal of Tropical Resources and Sustainable Science (JTRSS), 2026)
Over the past decade, research on fiber cement board (FCB) materials has experienced significant growth, driven by the demand for sustainable and high-performance construction materials. This bibliometric analysis examines global research trends in FCB studies from 2021 to 2025 by systematically retrieving publications from Scopus using predefined search strings related to fiber cement boards. The study applied filters for peer-reviewed articles published in English and utilized the bibliometric tools VOSviewer to analyze citation networks, co-authorship patterns, keyword co-occurrence, and thematic evolution. This approach enabled the identification of influential publications and authors, as well as the detection of emerging areas of interest. A comprehensive database search revealed a growing focus on incorporating various fiber reinforcements, including synthetic and natural fibers, to enhance mechanical, thermal, and durable properties. Notably, research on hybrid fiber reinforcement and alternative binders has gained prominence due to their potential to improve sustainability and structural performance. The study revealed a rising publication trend, peaking at nearly 650 articles in 2024, with China leading in output (854 publications) and citations (10,373), while Australia demonstrated the highest impact (19.9 citations per paper). Highly cited authors such as Zaid, O. (691 citations) and Kaplan, G. (471 citations) have made significant contributions, with Construction and Building Materials emerging as the dominant journal. These quantified insights highlight key contributors, research influence, and thematic shifts toward AI integration, sustainability, and fiber innovation in FCB studies. The results highlight the importance of material innovation, emphasizing the role of fiber-modified cement composites in advancing environmentally friendly and resilient construction practices. This study serves as a crucial reference for shaping future research and industrial applications in sustainable building materials.
Keywords: VOSViewer; natural fibers; construction material; building material; fiber reinforcement